BASIC KNOWLEDGE ON MUSCULAR EXPANSION, AND INSERTION OF THE PROFESSIONALS OF PHYSICAL EDUCATION: BIBLIOGRAPHICAL RESEARCH. (Fiep Bulletin - online, 2014)
The significant part of this study is part of a doctorate degree research thesis, which could make possible the entailing of the expansion study with the preparation of professionals in Physical Education; intending to elucidate that contents interest for their formation that allows a deep and safe performance, because the great use of the expansion for the people.The objective of it is to discourse the neuromuscular function and the mechanism directly involved to the adaptable process front to the stimulations of expansions and immobilization. We verify in the literature that, the muscle has the capacity to modify its form in response to a certain demand, being considered the individual with control to neuromuscular that answers to the necessities of the daily work, being that the soft tissues and joints, are continuously lengthened or shortened and its appropriate fulfillment is kept. When the movement is limited, there occurs shortening of soft tissues. Expansion is destined to get more profits of flexibility, capable of improving the action-reaction conditions, being the daily accomplishment of expansions for 30 minutes is enough to prevent the loss of flexibility and to keep the amplitude of the movement. The drawn out, soft, gradual expansions with a low number of repetitions are considered more efficient than brusque tractions with a great number of repetitions.As a final consideration, it is understood that it is necessary to offer this knowledge to the professionals of Physical Education, as these professionals are responsible for the physical qualification of the society.
Keywords: muscular expansion; professional formation; stress